Silicotungstate- or Phosphotungstate-Catalyzed Glycerol Esterification with Acetic Acid: A Comparison of Zinc and Tin Salts - Marcio Jose da Silva; Cesar Macedo Oliveira; Pedro Henrique da Silva Andrade; Neide Paloma Gonçalves Lopes (Reactions)
In this work, tin and zinc salts of silicotungstic and phosphotungstic acids were synthesized, characterized, and tested as catalysts for esterification reactions of glycerol with acetic acid (HOAc) to produce glycerol esters such as monoacetyl glycerol (MAG), which are used as additives in the pharmaceutical and food industries and in the manufacturing of explosives, or, in the case of di- or triacetyl glycerol (DAG and TAG), green bioadditives for diesel or gasoline. The activity of metal-exchanged salts (Zn, Sn) in H3PW12O40 and H4SiW12O40 heteropolyacids was evaluated in esterification reactions at room temperature. Among the catalysts tested, Sn2/3PW12O40 was the most active and selective toward the glycerol esters. The process’s selectivity can be controlled by changes to reaction conditions. The maximum selectivitiesy of DAG and TAG were 60% and 30%, respectively, using a 1:3 molar ratio of glycerol/HOAc and a Sn3/2PW12O40/673 K catalyst load of 0.4 mol%. Under these conditions, a glycerol conversion rate of 95% was observed and selectivity towards DAG and TAG was observed at 60% and 30%, respectively. The results were achieved after an 8 h reaction at a temperature of 333 K. The Sn3/2PW12O40/673 K catalyst demonstrated the highest efficiency, which was attributed to its higher degree of acidity.